Challenges in conducting qualitative research in health: A conceptual paper - Hamidreza Khankeh; Maryam Ranjbar; Davoud Khorasani-Zavareh; Ali Zargham-Boroujeni; Eva Johansson (Wolters Kluwer Medknow Publications, 2015)
Background: Qualitative research focuses on social world and provides the tools to study health phenomena from the perspective of those experiencing them. Identifying the problem, forming the question, and selecting an appropriate methodology and design are some of the initial challenges that researchers encounter in the early stages of any research project. These problems are particularly common for novices. Materials and Methods: This article describes the practical challenges of using qualitative inquiry in the field of health and the challenges of performing an interpretive research based on professional experience as a qualitative researcher and on available literature. Results: One of the main topics discussed is the nature of qualitative research, its inherent challenges, and how to overcome them. Some of those highlighted here include: identification of the research problem, formation of the research question/aim, and selecting an appropriate methodology and research design, which are the main concerns of qualitative researchers and need to be handled properly. Insights from real-life experiences in conducting qualitative research in health reveal these issues. Conclusions: The paper provides personal comments on the experiences of a researcher in conducting pure qualitative research in the field of health. It offers insights into the practical difficulties encountered when performing qualitative studies and offers solutions and alternatives applied by these authors, which may be of use to others.